Co-creating since 1990s: an qualitative analyses of the exploratory case study on a small private health IT company in North Norway though the prism of ANT. - Ikoev, Vitalii (UiT Norges arktiske universitet, 2020)
Digitalization of healthcare is done through development and delivery of health information technology, mobile health, wearable devices, telehealth, telemedicine, health portals, personalized medicine, or in other words – ehealth. Ehealth solutions are expected to improve the treatment process, improved safety, efficiency and quality, as well as empowerment of both patients and healthcare professionals. However, enthusiasm around technological innovation around e-health has not always been matched by uptake and utilization in practice. The amount of research on ehealth has been increasing last years, but there is little attention in research on how health IT solutions are being developed. There is a need for new knowledge on how vendors approach and work when developing solutions.